2019
DOI: 10.1007/s12035-019-01830-3
|View full text |Cite
|
Sign up to set email alerts
|

A Single Prior Injection of Methamphetamine Enhances Methamphetamine Self-Administration (SA) and Blocks SA-Induced Changes in DNA Methylation and mRNA Expression of Potassium Channels in the Rat Nucleus Accumbens

Abstract: The transition from occasional to escalated psychostimulant use is accelerated by prior drug exposure. These behavioral observations may be related to long-lasting transcriptional and/or epigenetic changes induced by the drug pre-exposure. Herein, we investigated if a single methamphetamine (METH) injection would enhance METH self-administration (SA) and impact any METH SA-induced epigenetic or transcriptional alterations. We thus injected a single METH dose (10 mg/kg) or saline to rats before training them to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Researchers in the Cadet laboratory have recently published several papers in which they attempt to mimic human MUD conditions in rodent models [ 53 , 55 , 107 , 108 , 109 ]. In those models, they have introduced an additional DSM5 criterion that is related to compulsive drug intake despite adverse consequences [ 107 ].…”
Section: Potassium Channels and Methamphetamine Use Disordermentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers in the Cadet laboratory have recently published several papers in which they attempt to mimic human MUD conditions in rodent models [ 53 , 55 , 107 , 108 , 109 ]. In those models, they have introduced an additional DSM5 criterion that is related to compulsive drug intake despite adverse consequences [ 107 ].…”
Section: Potassium Channels and Methamphetamine Use Disordermentioning
confidence: 99%
“…The potential role of potassium channels in METH taking behaviors was also investigated in a subsequent paper. In that paper, we tested the possibility that a single pre-exposure to METH could potentiate its intake during self-administration experiments [ 53 ]. Animals were therefore pre-treated with saline or METH prior to METH SA.…”
Section: Potassium Channels and Methamphetamine Use Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…Yuka et al (44) found that the rate of DNA methylation at six CpG islands of SHATI/NAT8L promoter sites is significantly higher in MA users when compared to healthy subjects. Jayanthi et al (45) reported that a single prior injection of MA enhanced MA self-administration (SA) and blocked SAinduced changes in DNA methylation and mRNA expression of potassium channels in the rat nucleus accumbens. MA produces a variety of epigenetic effects in the brain, which are seminal to establish long-lasting alterations in neuronal activity.…”
Section: Analysis Of Dmr Data Inferred the Role Of The Circadian Entrmentioning
confidence: 99%